COVID‐19 and liver disease - Sun, Jian; Aghemo, Alessio; Forner, Alejandro; Valenti, Luca (Liver international, 2020)
Since December 2019, patients with unexplained pneumonia have been found in Wuhan, Hubei Province, China, which was caused by a novel coronavirus that had not been previously identified (1). Tentatively defined as 2019 novel coronavirus (2019-nCoV), the pathogen has now been named Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) (2), while the disease termed Coronavirus Disease 2019 (COVID-19).